Hydrosorb® versus control (water based spray) in the management of radio-induced skin toxicity: Results of multicentre controlled randomized trial. Issue 2 (November 2015) - Bazire, Louis; Fromantin, Isabelle; Diallo, Alhassane; Lande, Brigitte de la; Pernin, Victor; Dendale, Remi; Fourquet, Alain; Savignoni, Alexia; Kirova, Youlia M.
Abstract: Purpose: To report the efficacy of Hydrosorb® versus control (water based spray) as topical treatment of grade 1–2 radiodermatitis in patients (pts) treated for early stage breast cancer (BC) with normo fractionated radiotherapy (RT). Patients and methods: BC pts were randomized to receive either Hydrosorb® (A) or water based spray (B). The primary endpoint was local treatment failure defined as interruption of RT because of skin radiotoxicity or change of local care because of skin alteration. Secondary endpoints were: evaluation of skin colorimetry, pain, quality of life. Results: Two-hundred seventy-eight pts were enrolled. There were 186 successfully treated pts. There were 60 "failures" in the Hydrosorb® arm, and 62 in the control arm ( p  = 0.72), but mostly without interruption of the RT. Twenty-four pts stopped RT for local care. The average absolute reduction of colorimetric levels between day 28 and day 0 was 4 in the Hydrosorb®, and 4.2 in the water spray groups, respectively ( p  = 0.36). Forty-eight patients in the Hydrosorb® arm had a VAS >2 versus 51 pts in the placebo arm, i.e. 34% and 38%, respectively ( p  = 0.45). A significant reduction of pain was observed on D 7 and D 21 in the Hydrosorb® arm. Conclusions: The present study showed no significant difference between Hydrosorb® and simple water spray in the treatment of acute radio-induced dermatitis even if there was a trend to an improvement in pain at the first weeks after the treatment. Systematic prevention measures and modern breast cancer radiotherapy techniques now allow excellent tolerability, but the place of topical treatment to optimize this tolerability has yet to be defined. It seems that the most important part of the skin care is the prevention of skin reactions using new adapted techniques, as well as strict hygiene.